MORTALITY FROM CARDIOVASCULAR PATHOLOGIES DEPENDING ON SEISMOLOGICAL ACTIVITY IN ZAGATALA REGION OF AZERBAIJAN - Efendiyeva, L.G. (World of Medicine and Biology, 2022)
Recent studies provide evidence of a link between seismological and geophysical activity and an increase in the number of cardiovascular accidents. The purpose of the work was to study the dependence of cardiovascular diseases mortality on helioseismic indicators in the Zagatala region of the Azerbaijan. In 2013, seismological information was obtained from 35 telemetry stations. To analyze the connection with diseases in the Zagatala region, 401 case histories of patients who died in 2013 from various cardiovascular diseases were examined. Results of the study showed that the largest number of deaths was: from a hypertensive crisis – at the age of 80–89 years (37.8 %), from acute cerebrovascular accident – at the same age (33.3%), from acute coronary syndrome – at the age of 70–79 years (43.4 %) and from acute heart failure – at the age of 80–89 years (40.7 %). The largest number of deaths was in all age categories due to acute coronary syndrome. The maximum number of deaths was at a magnitude of 1.1–2.0 ml (35.4 %). Thus, the study of seismic activity in various seismogenic zones will improve the prevention of morbidity and mortality from CVD.